Kedudukan Alat Bukti Website dalam Penanganan Tindak Pidana Terorisme (Studi Putusan Nomor 140/PID.SUS/2018/PN.JKT.SEL) - Gemaya Wangsa; Anak Agung Sagung Laksmi Dewi; I Wayan Arthanaya (Warmadewa Press, 2020)
The development of information technology and correspondence resulted in a shift in the format of print media to digital media, so that this growth was followed by the continuation of the development of a new criminal class that rode digital media in criminal acts of terrorism. This study aims to determine the regulations for the use of website evidence and the position of using website evidence in handling terrorism crimes in case number 140 / Pid.Sus / 2018 / PN.Jkt.Sel. This research uses a normative legal exploration method whose data comes from the determination related to the use of website evidence in Article 184 of the Criminal Code. The results of the research show that the determination of the exploitation of website evidence, which when based on Article 184 of the Criminal Procedure Code, means that electronic material is not classified as an abash instructional device classification, but if it is based on statutory regulations in a special crime, the electronic evidence media has resistance as a valid evidence, this can be seen in the provisions of Article 5 paragraph (1) of the ITE Law which are reaffirmed in the provisions of Article 44 of the ITE Law. Utilization of electronic evidence in the process of evidence in court is sourced from website evidence in law enforcement for criminal acts of terrorism in the Case Number 140 / Pid.Sus / 2018 / PN.Jkt.Sel scandal. Criminal Procedure, especially Article 184 of the Criminal Procedure Code, but has a judicial guideline that the judge cannot refuse to explore and decide the matters brought against him, provided that the law is unclear or non-existent, then the judges' rules should expose the meaning of continued and continuous law in the consortium, up to the provisions as contained in the ITE Law which regulates electronic instruction instruments as valid instruction devices.